2005
DOI: 10.1055/s-2004-830554
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Phosphorylation of Transcription Factor Elk-1 in Cultured Fibroblasts of a Patient with Premature Aging Syndrome and Insulin Resistance

Abstract: The effect of insulin and growth factor mediated signaling to gene regulation was investigated in cultured fibroblasts of a patient with a premature aging syndrome (metageria) and severe insulin resistance. Insulin receptor structure and function as well as major pathways activated by insulin, i.e. phosphatidyl inositol-3 kinase (PI-3 K) cascade or mitogen-activated protein kinase (MAPK) cascades, were functional. Inducibility of the proto-oncogene cfos, a representative endpoint of signaling pathways related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
0
7
0
4
Order By: Relevance
“…Variant rs2672598 created a binding site for the transcription factor ELK-1, whose activity was reported to be impaired in a patient with a premature form of aging and insulin resistance. 27 We hypothesize, then, that if the risk allele of the promoter SNP rs11200638 results in increased expression of HTRA1, 12,13 then the minor allele of rs2672598 might exert a protective effect by enabling the binding of ELK-1, which could downregulate the expression of HTRA1. On the other hand, the SNP rs2293870 is located in one of the HTRA1 binding domains for IGFs.…”
Section: Discussionmentioning
confidence: 99%
“…Variant rs2672598 created a binding site for the transcription factor ELK-1, whose activity was reported to be impaired in a patient with a premature form of aging and insulin resistance. 27 We hypothesize, then, that if the risk allele of the promoter SNP rs11200638 results in increased expression of HTRA1, 12,13 then the minor allele of rs2672598 might exert a protective effect by enabling the binding of ELK-1, which could downregulate the expression of HTRA1. On the other hand, the SNP rs2293870 is located in one of the HTRA1 binding domains for IGFs.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence using this animal model suggest that an altered management of oxidative stress is strongly related to its increased longevity (Hsieh et al 2002;Madsen et al 2004). Supporting evidence for the regulatory effect of Elk-1 is provided in a report by Knebel et al (2005), who found that basal and inducible phosphorylation of Elk-1 was impaired in cultured fibroblasts of a patient with premature aging syndrome and insulin resistance (Knebel et al 2005).…”
Section: Screening For Age-and Cr-related Genesmentioning
confidence: 91%
“…Nuclear extracts from fibroblasts of the patient and controls, or HepG2 cells were prepared as described [11]. …”
Section: Methodsmentioning
confidence: 99%
“…MAPK activity assays and western blotting with polyclonal anti-Akt or anti-phospho Akt antibody (New England Biolabs, Frankfurt, Germany) or polyclonal anti-MAPK antibody (BD Transduction; Heidelberg, Germany) were performed as described [11]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation